Indoor localization and navigation for blind persons using visual landmarks and a GIS - Serrão, M. (2013)
In an unfamiliar environment we spot and explore all available information which might guide us to a desired location. This largely unconscious processing is done by our trained sensory a nd cognitive systems. These recognize and memorize sets of landmarks which allow us to create a mental map of the envi ronment, and this map enables us to navigate by exploiting very few but the most important landmarks stored in our memory. We present a system which integrates a geographic information system of a building with visu al landmarks for localizing the user in the building and for tracing and validating a route for the user's navigation. Hence, the developed system complements the white cane for improving the user's autonomy during indoor navigation. Although de signed for visually impaired persons, the system can be used by any person for wayfinding in a complex building.